An analysis of zoo visitors' favourite and least favourite animals. (October 2016) - Carr, Neil
Abstract: This paper provides an assessment of which animals visitors to zoos prefer and the reasons why this is the case. It expands on previous research that has tended to examine animal attractiveness indirectly and focused on attractiveness rather than also examining unattractiveness as a distinct issue. The paper is based on the results of a survey distributed to a convenience sample of 444 visitors to Durrell Wildlife Park, located on the island of Jersey, UK, immediately after their visit to the zoo. The study was undertaken during the summer of 2013. The results show that mammals are the favourite animals of visitors to zoos while reptiles and birds are the least favourite animals. Animals that are perceived to be entertaining and cute are clearly favoured by zoo visitors while those perceived to be boring and/or hard to see tend not to appeal. Other unappealing animal characteristics include scary and smelly. Highlights: Zoo visitors' favourite animals are mammals while their least favourite are reptiles and birds Zoo visitors' favourite animals are perceived to be entertaining, and cute and cuddly Zoo visitors' least favourite animals are perceived to be boring and hard to see